Characterization of mesenchymal stem cells derived from adipose tissue of a cougar (Puma concolor) - Echeverry, Diana Maritza (Anim Reprod, 2020)
Adipose derived mesenchymal stem cells (AMSCs) have been isolated from domestic and wild cats. For wild cats, the isolation of AMSCs has been reported in the black-footed cats (Felis nigripes) and guigna (Leopardus guigna). Stromal vascular fraction (SVF) isolated from cougar adipose tissue have been used to restore elbow functionality in the cougar (Puma concolor) but multipotent characteristics of these cells have not been described. The present study describes for the first time the isolation and characterization of mesenchymal stem cells derived from adipose tissue of cougar. AMSCs and fibroblasts from six months female cougar were isolated and cultured in DMEM/F12, supplemented with FBS 10% + 1% Antibiotic/Antifungal + 2.4 mM L-Glutamine + 2.4 mM pyruvate up to passage 5. Expression of pluripotent and surface marker genes was evaluated at mRNA level. Mesodermal differentiation (adipogenic, osteogenic and chondrogenic) was described. AMSCs expressed mRNA of pluripotent genes Oct4, Nanog, Sox2 and Klf4 and surface markers Cd44, Cd90, Cd105 and MHCII. Fibroblasts showed similar mRNA expression with the exception of Sox2. AMSCs obtained from cougar exhibit multipotency features similar to domestic cats MSC, nevertheless, other analyses are required. AMSCs from cougar could be a source of interest for treatment of individuals that remain in captivity or arrive to wildlife rehabilitation centers.